2006
DOI: 10.1182/blood-2005-06-2308
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the core region of 5′ HS2 of the mouse β-globin locus control region reveals a distinct effect in comparison with human β-globin transgenes

Abstract: The ␤-globin locus control region (LCR) is a large DNA element that is required for high-level expression of ␤-like globin genes from the endogenous mouse locus or in transgenic mice carrying the human ␤-globin locus. The LCR encompasses 6 DNaseI hypersensitive sites (HSs) that bind transcription factors. These HSs each contain a core of a few hundred base pairs (bp) that has most of the functional activity and exhibits high interspecies sequence homology. Adjoining the cores are 500-to 1000-bp "flanks" with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…In the ␤-globin locus, six hypersensitive sites (HS1-6) of the LCR, the upstream 5Ј HS-60/-62, and the downstream 3Ј HS1 together form an active chromatin hub (30), where it is widely thought that the LCR and promoters associate with each other. In the ␤-globin LCR, the deletion of HS2, which acts as an enhancer in transient reporter assays, leads to a slight decrease in the expression of the Bmajor and Bminor genes in the fetal liver and adult peripheral blood definitive erythroid cells (31,32). In the present study, we identified six HS sites within the CCR.…”
Section: Discussionmentioning
confidence: 56%
“…In the ␤-globin locus, six hypersensitive sites (HS1-6) of the LCR, the upstream 5Ј HS-60/-62, and the downstream 3Ј HS1 together form an active chromatin hub (30), where it is widely thought that the LCR and promoters associate with each other. In the ␤-globin LCR, the deletion of HS2, which acts as an enhancer in transient reporter assays, leads to a slight decrease in the expression of the Bmajor and Bminor genes in the fetal liver and adult peripheral blood definitive erythroid cells (31,32). In the present study, we identified six HS sites within the CCR.…”
Section: Discussionmentioning
confidence: 56%
“…41 However, deletion of HS2 led to only a 30% decrease in ␤-globin transcription. 41,42 In contrast, KD of PRMT1 has a more drastic effect, more similar to deletion of the entire LCR. The effect is likely because PRMT1 is recruited not only to the LCR but also to the ␤ maj -promoter, and possibly to other genes as well.…”
Section: Discussionmentioning
confidence: 97%
“…This may explain why small deletions of LCR core regions in transgenic models have a devastating effect on transcription compared with larger deletions, 4,11,12,[38][39][40] but that no such difference is observed at the endogenous locus. 41 …”
Section: Hs Contributions To Lcr Functionmentioning
confidence: 99%